Efficacy and Safety of Eculizumab for Paroxysmal Nocturnal Hemoglobinuria: A Systematic Review and Meta-Analysis. Issue 6 (26th August 2021) - Zhou, Shuang; Dong, Xiu; Chen, Chaoyang; Ma, Lingyun; Wu, Ye; Zhou, Ying; Cui, Yimin
Abstract : Background: Eculizumab is indicated for the treatment of paroxysmal nocturnal hemoglobinuria (PNH). This study aimed to evaluate the efficacy and safety of eculizumab in patients with PNH. Methods: PubMed, EMBASE, The Cochrane Library, and ClinicalTrials .gov were searched for prospective interventional studies treating PNH with eculizumab. The primary outcome was the change in lactate dehydrogenase (LDH) levels, whereas secondary outcomes included the change in hemoglobin (Hb) levels, transfusion rates, and adverse drug events. Results: Patients (n=235) from 6 studies were included in this meta-analysis. LDH and Hb levels and transfusion rates decreased significantly at 12, 26 weeks, 12, 15, and >15 months. The most frequent adverse events included nasopharyngitis (effect size [ES]: 0.53; 95% confidence intervals [CI]: 0.47 to 0.60; P =0.00), headache (ES: 0.47; 95% CI: 0.25 to 0.69; P =0.00), upper respiratory tract infection (ES: 0.37; 95% CI: 0.27 to 0.46; P =0.00), nausea (ES: 0.31; 95% CI: 0.24 to 0.38; P =0.00), fatigue, diarrhea, cough, pyrexia, abdominal pain, pain in extremities, and contusion. Conclusion: Eculizumab is an effective and well-tolerated treatment for patients with PNH. It is effective at decreasing LDH levels and transfusion rates while increasing Hb levels. Further studies are needed to explore the safety of eculizumab.